The Cost of Being Female: Critical Comment on Block - Sayers, Rachel C. (2012)
Women currently earn 77 cents for every dollar earned by men. Explanations abound for why, exactly, this wage gap exists. One of the more potent justifications attributes this pay differential to the unequal effects of marriage on the sexes: the marital asymmetry hypothesis. However, even when marital status is accounted for, a small but significant residual gap remains. This article argues that this is the result of social factors. Entrenched societal sexism causes all of us to harbor unconscious bias about the capabilities and proper gender roles of women. This bias, in turn, leads us to discount work completed by females, especially in professional environments. Employers are not immune from this effect, and the undervaluation of female ability affects hiring practices, leading to the residual wage gap.
Keywords: Marital asymmetry; Sexism; Wage differentials; pay gap; Discrimination; Feminism